RESILIENT MODULUS, FATIGUE, AND PERMANENT DEFORMATION PERFORMANCE OF ASPHALTIC CONCRETE WEARING COURSES (AC-WC) USING STARBIT E-55 MODIFIED ASPHALT - Kunto Suryoaji, Tosan
It is important to have strong pavement structure of the road to support high traffic load, hence a proper pavement material design is needed. One of pavement structure layers is Asphalt Concrete Wearing Course (AC-WC). Therefore, this research aims to evaluate the performance of Asphalt Concrete Wearing Course mixtures using Starbit E-55 modified asphalt based on resilient modulus, fatigue failure criteria, and permanent deformation. The asphalt used in this research are asphalt Pen 60/70 and Starbit E-55 modified asphalt. The basic properties of asphalt and aggregates were measured by standard test, based on Indonesian’s Standard of Hot-mix asphalt mixtures, while the performance of mixture was measured by Standard Marshall test, Marshall Immersion test, UMATTA’s Resilient modulus test, and Wheel Tracking Machine test. Mixture performance according to the Marshall test shown that the value of Marshall Stability were 1019 kg (Pen 60/70), 1262 kg (Starbit E-55). The result of Marshall Immersion test shown that the highest value of 91,56% was on Starbit E-55 mixture. The results of Resilient Modulus test on Starbit E-55 mixture were 3232 MPa at 25°C, 793 MPa at 35°C, and 390 MPa at 45°C, which is the highest value than others. The results of Fatigue test on Starbit E- 55 mixture were 63719 cycles at 600??, 47848 cycles at 650??, and 33399 cycles at 700??, which is the highest value than others. The result of Wheel Tracking test on Starbit E-55 mixture shown the total deformation was 0,47 mm at 25°C, 1,59 mm at 45°C, and 1,54 mm at 60°C. Generally, the result of this research shown that Starbit E-55 modified asphalt mixture had a better performance at high temperature. The mixture of Starbit E-55 modified asphalt is better than Pen 60/70 asphalt mixture due to its structural capacity and the resistance of fatigue and deformation (rutting) were higher than others and has fulfilled the specification.